Drug-Induced Naïve iPS Cells Exhibit Better Performance than Primed iPS Cells with Respect to the Ability to Differentiate into Pancreatic β-Cell Lineage - Kiyokawa, Yuki (J Clin Med, 2020)
Pluripotent stem cells are classified as naïve and primed cells, based on their in vitro growth characteristics and potential to differentiate into various types of cells. Human-induced pluripotent stem cells (iPSCs, also known as epiblast stem cells [EpiSCs]) have limited capacity to differentiate and are slightly more differentiated than naïve stem cells (NSCs). Although there are several in vitro protocols that allow iPSCs to differentiate into pancreatic lineage, data concerning generation of β-cells from these iPSCs are limited. Based on the pluripotentiality of NSCs, it was hypothesized that NSCs can differentiate into pancreatic β-cells when placed under an appropriate differentiation induction condition. We examined whether NSCs can be efficiently induced to form potentially pancreatic β cells after being subjected to an in vitro protocol. Several colonies resembling in vitro-produced β-cell foci, with β-cell-specific marker expression, were observed when NSC-derived embryoid bodies (EBs) were induced to differentiate into β-cell lineage. Conversely, EpiSC-derived EBs failed to form such foci in vitro. Intrapancreatic grafting of the in vitro-formed β-cell foci into nude mice (BALB/c-nu/nu) generated a cell mass containing insulin-producing cells (IPCs), without noticeable tumorigenesis. These NSCs can be used as a promising resource for curing type 1 diabetes.